Training and Assistance in Making Audio Visuals Formation of Nationalism Character in Elementary School Teachers Communities of Progressive School Movements in the Daerah Istimewa Yogyakarta Based on Desktop Applications - Wiwik Handayani; Ika Korika Swasti; Tri Lathif; Ari Setya Budi; Muhammad Khalif (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
“Gerakan Sekolah Berkemajuan (GESEKAN)” is a community formed for the principal's performance, one of which is to form a nationalist character as his vision. This community needs character learning to build school branding because of changing conditions and skills, difficulties in translating character learning ideas to meet learning outcomes, especially in attitude formation, and difficulties in finding assistance and training in making AVA Media, it's AVA offered for facilitating the learning of character building with UPN East Java as the facilitator. As a result, this training provided new insights and knowledge for Juniors School Teachers in the “Gerakan Sekolah Berkemajuan” in the Special Region of Yogyakarta. This training helped resolve the limitations of their abilities